Systematized verrucous epidermal nevus in a six-year-old girl. - Nayak, S.; Jindal, A. (European Journal of Pediatric Dermatology, 2014)
Epidermal nevi are nevus lesions consisting of any component of the epidermis including adnexal structures. They are classified according to the clinical and pathological findings, the extent of skin involvement, presence of inflammation and possible involvement of other organs. The lesions are benign but require treatment for cosmetic purposes. Here we are reporting a case of systematized verrucous epidermal nevus in a six years old female child.